The Effect of Graphene Oxide Biomass as Filtration Loss Control Agent of Water-Based Mud Fluid - Mursyidah; Nur Hadziqoh; Binti Mod Zaid, Hasnah; Rahmayeni, Foni (International Journal of Natural Science and Engineering, 2023)
Water-based drilling fluids are complex chemical systems that are essential for water drilling excavation. Biomass of Graphene Oxide (GO) is a submicrometer-thick material with unique and specific properties. GO can be entirely impermeable to liquids, vapors, and gases. It has water dispersibility and a huge specific surface area that is the potential material suitable for filtration loss control agents of water-based mud fluid. This study aims to analyze the effectiveness of Oil Palm Shell Graphene Oxide Biomass as an additif material to filtration control in water-based mud fluid. Making  GO biomass sample starts from biomass Oil Palm Shell into graphite biomass, then the graphite biomass was sinthesized using an ultrasound-assisted liquid Phase Exfoliation (LPE) method to obtain thin GO biomass. Graphite biomass and GO biomass were characterized using FTIR, UV-Vis Spectroscopy and SEM-EDX. Drilling fluid samples with graphite biomass and GO biomass were prepared by adding 0.5 gr Graphite biomass and GO biomass into the based fluid (water-based bentonite fluid), The Filtration loss and the mud cake thickness of all the samples are measured and compared. Based on the measurement results, GO biomass additive is very effective in reducing fluid loss compare to graphite biomass additif. The volume of fluid lost was decreases from 13.9 ml to 10.8 ml compare to graphite biomass which was only able to decrease it to 12,3 ml.